Bis(3)-tacrine inhibits the sustained potassium current in cultured rat hippocampal neurons - Wen, R-J; Huang, D; Zhang, Y; Liu, Y-W (Physiological research, 2017)
Bis(3)-tacrine is a dimeric AChE inhibitor derived from tacrine with a potential to treat Alzheimer's disease. It was recently been reported to act as a fast off-rate antagonist of NMDA receptors with moderate affinity. In the present study, we aimed to explore whether bis(3)-tacrine could modulate the function of native sustained potassium current in cultured rat hippocampal neurons using whole-cell patch-clamp technique. We found that bis(3)-tacrine inhibited the amplitude of sustained potassium current in a reversible and concentration-dependent manner, with a potency two orders of magnitude higher than that of tacrine. The inhibition was voltage-independent between 0 to +60 mV. The IC(50) values for bis(3)-tacrine and tacrine inhibition of sustained potassium current were 0.45+/-0.07 and 50.5+/-4.8 microM, respectively. I-V curves showed a more potent inhibition of sustained potassium current by bis(3)-tacrine (1 microM) compared to tacrine at the same concentration. Bis(3)-tacrine hyperpolarized the activation curve of the current by 11.2 mV, albeit leaving the steady-state inactivation of the current unaffected.
Keywords: Membrane Potentials; Cholinesterase Inhibitors; potkani Sprague-Dawley; elektrická stimulace; takrin; draslíkový kanál Kv1.2; vztah mezi dávkou a účinkem léčiva; Kv1.2 Potassium Channel; Electric Stimulation; neurony; membránové potenciály; krysa rodu Rattus; Hippocampus; kultivované buňky; Animals; zvířata; Neurons; Rats; Cells, Cultured; Tacrine; Dose-Response Relationship, Drug; cholinesterasové inhibitory; hipokampus; Rats, Sprague-Dawley